Analisis Faktor-Faktor yang Mempengaruhi Tingkat Partisipasi Angkatan Kerja Perempuan di Provinsi Riau - Anannty, Sindy Febriana; Kusuma, Airlangga Surya; Fairuz, Cantika Deanda; Syawalita, Naia; Avianti, Dina; Caroline, Fadiah Syifa (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The study aims to analyze the factors that influenced the participation rate of women in the labour force in Riau Province from 2012 to 2022. The design of the study uses quantitative methods with double linear regression analysis. Objects of research include Women’s Workforce Participation Rate (TPAKP), Average Age of Women in School (RLSP), Provincial Minimum Wage (UMP), and Women’ s Productive Age (UPP). The sample of the research consists of secondary data obtained from various official sources with a total of 40 data. The research contributes originality in the regional economic context, with regard to the participation of women in the labour force in Riau Province.